Tantangan Perlindungan Hukum Desain Industri dalam Penyelesaian Sengketa di Indonesia - Donna Loedi Ellizabeth; Jufanka Zola Eka Febrianti; Yulia Putri Syifa; Nadhira Wahyu Adityarani (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The enforcement of legal protection for industrial designs in Indonesia continues to face various challenges, both in terms of legal substance and implementation mechanisms. This study aims to analyze in depth the forms of challenges in the legal protection of industrial designs and to examine the dispute resolution system currently applied in Indonesia. The research method used is a normative juridical approach, with data collected through literature studies and analysis of relevant cases. The findings indicate that the main challenges in the enforcement of industrial design law include weak sanction enforcement against violators, low public awareness of the importance of design registration, complex administrative procedures, and the limited capacity of competent dispute resolution institutions. Moreover, under the Indonesian legal system, industrial design protection is granted through exclusive rights after registration; however, the implementation of these rights remains suboptimal. Industrial design disputes can be resolved through litigation or alternative dispute resolution mechanisms such as mediation, which are more efficient and oriented toward peaceful solutions. The conclusion of this study emphasizes the importance of reforming the legal protection system and strengthening institutional capacity to provide legal certainty for industrial design rights holders and to establish an equitable and effective dispute resolution system.